Cool melons--turn to frogs! : the life and poems of Issa - Gollub, Matthew; Stone, Kazuko G. (New York : Lee & Low Books, 1998)
A biography and introduction to the work of the Japanese haiku poet whose love for nature finds expression in the more than thirty poems included in this book.
Kirkus Review
4.7
K-3
Keywords: Kobayashi, Issa, -- 1763-1827 -- xJuvenile literature; Poets, Japanese -- Edo period, 1600-1868 -- Biography -- Juvenile literature; Kobayashi, Issa, -- 1763-1827.; Poets, Japanese; Haiku; Kobayashi, Issa, -- 1763-1827.; Japanese poets; Haiku